Integrasi Teori Manajemen dalam Pendidikan Islam: Perspektif dan Implementasi - Muhammad Ali Subkan (Journal on Education, 2025)
Islamic education plays an important role in shaping individuals who are knowledgeable and have noble character. In the context of managing Islamic educational institutions, the application of modern management theories integrated with Islamic values ​​is very relevant to improve the efficiency and quality of education. This study aims to examine how Islamic management principles can be integrated into the operations of Islamic educational institutions, explore implementation strategies, and provide practical recommendations for managers. This study uses a qualitative approach with a descriptive-analytical method, where case studies are conducted at several Islamic educational institutions that have implemented Islamic management principles. Data were collected through in-depth interviews, participant observation, and documentation analysis. Thematic analysis techniques were used to identify key themes related to the management of Islamic education. The results of the study indicate that the integration of Islamic management theories, such as the principles of monotheism, justice, deliberation, trust, efficiency, and ihsan, can improve the effectiveness of resource management, strengthen the spiritual dimension in decision making, and create a holistic learning environment. In conclusion, the application of Islamic management can enrich the management of Islamic educational institutions, improve the quality of education, and support the sustainability of the organization while maintaining Islamic values. Practical recommendations are provided to help Islamic educational institutions face modern challenges in Islamic value-based management. Keywords: Islamic education management, integration, Islamic values, Islamic management.